Social Process and Cohabitation: A Trend of the New Generations - Ounjit Laila, Wilailak (International Journal of Engineering and Technology, 2018)
Cohabitation is a phenomenon which has taken place relatively recently in Thailand and is likely to spread and increase gradually in the future. Currently there are very few systematic studies on cohabitation among adolescents in Thailand and information has been obtained mostly from public media such as; newspapers, television programs and the internet. This qualitative and quantitative research aims to study the social process and cohabitating among Thai Adolescents. One thousand three hundred and twenty-eight respondents, who were in years one to four of their studies, were selected to participate, using a stratified random sampling technique. The survey was designed to use questionnaires to gather information from the respondents. In addition, semi-structured interviews were carried out with students, to provide a more in-depth understanding of the issues under study. The conceptual framework for this study was derived from empirical observation and intuition; imitation, social contact and social control. The results of the study revealed that there is a prevalence of cohabitation among Thai Adolescents. The significant factors that influenced the students’ cohabitation are foreign cultures, including American, Japanese and Korean culture (45.12%).  Their peers' cohabitation did not play a key role in the respondents wanting to experience cohabitation. The belief that traditional Thai women should reserve themselves for marriage was accepted among respondents (44.75%). Many of the respondents indicated that their families opposed cohabitation. Additionally, sexual behavior of Thai women is limited in the traditional norm. Cohabitation is considered as untraditional and teenagers are dating each other secretly (42.13 %). The information available and institutional education on the prevention of Sexually Transmitted Infections and Unwanted Pregnancies, allow adolescents to better understand the consequences of pre-marital sexual relationships (45.92%).